Efficacy of propofol for the prevention of emergence agitation after sevoflurane anaesthesia in children: A meta-analysis - Xiao, Yinggang; Jin, Xuening; Zhang, Yang; Huang, Tianfeng; Zhou, Luojing; Gao, Ju (Frontiers in Surgery, 2022)
Abstract Background: Emergence agitation (EA) is a common postoperative behavioral disorder, predominantly in pediatric patients, after sevoflurane general anesthesia. This study was aimed at assessing propofol’s efficacy and clinical conditions established for preventing EA in children under sevoflurane anesthesia. Methods: Randomized controlled trials (RCTs) that comparatively investigated propofol and control treatment in terms of efficacy and safety on administration at the end of surgery and examinations to prevent EA in children under sevoflurane anesthesia were searched. The sources accessed included PubMed, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov. Furthermore, manual searches were performed to identify studies; the last review was conducted on March 21, 2022. When the risk of bias assessment of trials was performed with the Cochrane Risk of Bias Tool, we calculated risk ratios (RRs) with 95% confidence intervals (CIs) for EA incidence and mean differences (MDs) with 95% CI for continuous data. Results: We included 12 RCTs with 1103 children. EA incidence (RR: 0.51, 95% CI: 0.39 to 0.67) and Pediatric Anesthesia Emergence Delirium scores (MD: -3.14, 95% CI: -4.37 to -1.92) were lower in the propofol group. Subgroup analyses showed lower EA incidences with 3 mg/kg propofol (RR: 0.22, 95% CI: 0.13 to 0.38) without extension of the PACU time (MD: 4.97, 95% CI: -0.84 to 10.78) in the laryngeal mask airway (LMA; RR: 0.52, 95% CI: 0.36 to 0.77) and spontaneous breathing (RR: 0.36, 95% CI: 0.21 to 0.62) groups. Discussion: We confirmed that a prophylactic dose of propofol prevented EA and decreased its severity in children under sevoflurane anesthesia. Furthermore, several conditions such as 3 mg/kg propofol, LMA, and spontaneous breathing, potentially contributed to EA prevention. Clinical trial registration: PROSPERO CRD42021274692.